2021
DOI: 10.3389/fpsyt.2021.748069
|View full text |Cite
|
Sign up to set email alerts
|

Telemental Health Use in the COVID-19 Pandemic: A Scoping Review and Evidence Gap Mapping

Abstract: Background: The COVID-19 pandemic has highlighted telemedicine use for mental illness (telemental health).Objective: In the scoping review, we describe the scope and domains of telemental health during the COVID-19 pandemic from the published literature and discuss associated challenges.Methods: PubMed, EMBASE, and the World Health Organization's Global COVID-19 Database were searched up to August 23, 2020 with no restrictions on study design, language, or geographical, following an a priori protocol (https://… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 213 publications
2
43
0
4
Order By: Relevance
“…Finally, these results align with a growing body of literature demonstrating the effectiveness of using a telehealth platform for providing mental health services [ 79 - 82 ]. Clinical decision support tools have demonstrated efficacy in depression outcomes in primary care and general practices [ 83 - 85 ].…”
Section: Discussionsupporting
confidence: 81%
“…Finally, these results align with a growing body of literature demonstrating the effectiveness of using a telehealth platform for providing mental health services [ 79 - 82 ]. Clinical decision support tools have demonstrated efficacy in depression outcomes in primary care and general practices [ 83 - 85 ].…”
Section: Discussionsupporting
confidence: 81%
“…Because access to in-person treatment and primary care was limited, alternatives for in-person treatment were quickly introduced at the start of the pandemic in order to maintain continuity and accessibility of care [ 64 ]. We refer to ‘online treatment’ as real-time, remote clinical services between healthcare providers and patients, including video-telephony.…”
Section: Online Treatmentmentioning
confidence: 99%
“…Body image concerns, technological difficulties, and lack of privacy reduced satisfaction with online treatment [ 30 , 32 ]. Those with limited access to online services (e.g., because of unfamiliarity or unavailability) and those living in middle- and low-income countries are currently being overlooked – both in studies and in online treatment options [ 64 , 78 ▪ , 79 ]. None of the studies reported on experiences with online therapy prior to the pandemic.…”
Section: Online Treatmentmentioning
confidence: 99%
“…Explorations in factors affecting quality, satisfaction, accessibility, and outcomes have proliferated since the beginning of the pandemic. A recent review on TMH during the COVID-19 pandemic highlighted the challenge of regulations and standard of care, effectiveness, privacy and confidentiality ( Abraham et al, 2021 ). However, the growing consensus is that TMH is a reasonable modality of health care delivery, and that patients and providers are more accepting of TMH since the pandemic.…”
Section: Introductionmentioning
confidence: 99%